PENGGUNAAN BAHASA INDONESIA YANG BAIK DAN BENAR DENGAN KEMAMPUAN BERPIDATO - Ikawati, Erna (IAIN Padangsidimpuan, 2014)
Ability in speech is strong enough affected by mastering good and correct language. Teaching a good and correct language needs full attention in order to be better in speech. A teacher must focus and motivateÂ students to apply good and correct language aspecially in speech.